Diagnosis of generation and handling of solid residuals in the University of Quindío (Revista de Investigaciones Universidad del Quindío, 2010)
The generation of solid residuals is one of the main environmental and health problems, it evidences the use that we make of this planet and the ecological print that we leave in it. In Colombia, it is considered that at national level are generated 30.886 daily tons approximately, the department of Quindío 531 tons per day of solid residuals, of which Armenia represents 37% (196 tons per day). The generation of solid residuals in the University of Quindío is of 210 Kg per day, of which 16,8 kg (8%) are biodegradable or organic, 3,4% (7,2 kg) are recyclable (paper), the biggest volume is ordinary (it includes inert), 182 Kg that are equal to 86,66%, dangerous (bio-sanitary) they are 3,8 Kg (1,9%). That is to say there are generated up to 63 to 76 tons of solid residuals per year. The generation of solid residuals per capita is 23,33 gr per day. In one year it is up to 8 to 9,5 kg per capita, this was calculated identifying the university population in 8.000 people. The objective of this project was to elaborate the diagnosis of the generation and handling of solid residuals in the University of Quindío, with the purpose of design and propose a System for Environmental Administration.
Keywords: Solid residuals; solid residuals management; system of environmental administration